Implementasi Personal Digital Inquiry berbantuan Infografis untuk meningkatkan literasi sains pada materi ekosistem - Ratih Nur Sholihah; Kusnadi; Bambang Supriatno (Postgraduate, University of Mataram, 2023)
This type of research is a quasi-experimental study,the research subjects were 70 Grade X students of SMAN X Cimahi. The purpose of this study was to see the effect of applying the Infographic-assisted Personal Digital Inquiry learning strategy on scientific literacy. The results of implementing an infographic-assisted personal digital inquiry learning strategy for science literacy test, the experiment class about indicator explaining the phenomenon scientifically has changed the medium category with an average value 65.14. For indicators evaluating and designing scientific questions even though there is the average value 54.28 still in the medium category on the results. And then, the average value of each indicator aspect of scientific literacy competence has changed, namely the indicator of interpreting data and evidence scientifically from the high category with an average value of 80.6. The Gain score obtained by the experimental class around 69.2% shows that these results are quite effective in learning. This can be seen from the Asymp value. Sig. (2-Tails) ranging from 0.000 <0.05, meaning that there is a significant differences in students' scientific literacy abilities using infographic-assisted digital personal inquiry learning strategies.